Safety management of construction plant and machinery / Husrul Nizam Husin @ Husain - Husin @ Husain, Husrul Nizam (2005)
These past few years has seen that the government has made an effort on executing safety and health policies through the enforcement of guidelines as well as conducting site safety seminars and certifications. Ranked as a second industry in Malaysia that contribute to highest percentage of accidents at the worksite, the impact of loss of profit and unhealthy workplace affect the construction industry. Statement from statistic has shown that construction plant and machineries becomes one ofthe caused for the accidents. Therefore this research as titled “Safety Management for Construction Plant And Machinery” tries to delineate the relationship and the importance of safety management for construction plant and machinery by designing and proposing an application model that can be used as guidelines for the management. Directive method is used in order to obtain the findings of the research.